Polyfunctional tumor-reactive T cells are effectively expanded from non-small cell lung cancers, and correlate with an immune-engaged T cell profile. (2nd November 2019) - De Groot, Rosa; Van Loenen, Marleen M.; Guislain, Aurélie; Nicolet, Benoît P.; Freen-Van Heeren, Julian J.; Verhagen, Onno J.H.M.; Van Den Heuvel, Michel M.; De Jong, Jeroen; Burger, Patrick; Van Der Schoot, C.Ellen; Spaapen, Robbert M.; Amsen, Derk; et al.
ABSTRACT: Non-small cell lung cancer (NSCLC) is the second most prevalent type of cancer. With the current treatment regimens, the mortality rate remains high. Therefore, better therapeutic approaches are necessary. NSCLCs generally possess many genetic mutations and are well infiltrated by T cells (TIL), making TIL therapy an attractive option. Here we show that T cells from treatment naive, stage I-IVa NSCLC tumors can effectively be isolated and expanded, with similar efficiency as from normal lung tissue. Importantly, 76% (13/17) of tested TIL products isolated from NSCLC lesions exhibited clear reactivity against primary tumor digests, with 0.5%-30% of T cells producing the inflammatory cytokine Interferon (IFN)-γ. Both CD4 + and CD8 + T cells displayed tumor reactivity. The cytokine production correlated well with CD137 and CD40L expression. Furthermore, almost half (7/17) of the TIL products contained polyfunctional T cells that produced Tumor Necrosis Factor (TNF)-α and/or IL-2 in addition to IFN-γ, a hallmark of effective immune responses. Tumor-reactivity in the TIL products correlated with high percentages of CD103 + CD69 + CD8 + T cell infiltrates in the tumor lesions, with PD-1 hi CD4 + T cells, and with FoxP3 + CD25 + CD4 + regulatory T cell infiltrates, suggesting that the composition of T cell infiltrates may predict the level of tumor reactivity. In conclusion, the effective generation of tumor-reactive and polyfunctional TIL products implies that TIL therapy will be a successful treatment regimen for NSCLC patients.